Designing policy mixes for the sustainable management of water resources - Bulian, Simon; Vogeler, Colette Sophie; Metz, Florence (Journal of environmental policy and planning, 2022)
Today’s complex policy problems are strongly characterized by interdependencies across sectors. Such interdependencies hamper the sustainable management of natural resources such as water. The protection of water resources exhibits manifold interlinkages, often with energy and food policy. Interdependent policy problems entail trade-offs across policy sectors and therefore present decision-makers with a major challenge. In order to address this, the design of sustainable policy mixes should produce synergetic effects that contribute to both the protection of water resources and achieving the objectives of other interlinked policy sectors. However, it remains unclear why some policy mixes show significant flaws that prevent the achievement of sustainable outcomes. The contributions of this special issue step into this research gap and aim to explain variation in policy mixes and their contribution to sustainability.